Preparation method and application of geopolymer microsphere adsorbent
By using geological polymer microspheres prepared by industrial solid waste and kitchen waste, the problems of low adsorption performance, high cost and difficult recycling of phosphate removal in water bodies are solved, and efficient, environmentally friendly and economical phosphate adsorption effect is achieved.
Patent Information
- Application Number
- CN202510201587.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art has problems in the removal of phosphate in water bodies with low adsorption performance, high cost, and may cause secondary pollution of water bodies and difficult to recycle adsorbent materials.
Industrial solid waste fly ash and slag are used as raw materials, combined with kitchen waste egg shells and oyster shells as pore-making agents and adsorption sites, and geological polymer microspheres are prepared by mechanical slow stirring and suspension polymerization to be used for adsorption of phosphate in water.
The phosphate adsorption effect is achieved with low cost, pollution-free and convenient recycling, which improves adsorption performance, reduces production costs, and solves the problem of recycling and utilization of adsorbent materials.
Smart Images

Figure CN119838584A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid waste treatment-environmental protection technology, and specifically relates to a preparation method and application of a geopolymer microsphere adsorbent. Background Art
[0002] Phosphorus (P), as an essential nutrient for life, is a scarce and non-renewable resource. However, if not properly handled, the accumulation of phosphorus in water can lead to severe eutrophication, accelerate the spread of algae, and threaten the growth of aquatic organisms and the survival of animals. With the implementation of strict phosphorus emission standards worldwide, the efficient removal of phosphorus has become more urgent. At the same time, phosphorus is a non-renewable nutrient element necessary for the development of all biological organs, and it is estimated that phosphorus in available minerals may be exhausted in less than a hundred years. Therefore, the recycling of phosphorus has always been an environmental issue of widespread concern.
[0003] At present, there are many methods for removing phosphate from water bodies, such as chemical precipitation, adsorption, bioremediation, ion exchange, etc. Among them, the adsorption method has the advantages of simple process, high efficiency, and easy access to materials. The materials commonly used to remove phosphate from water bodies include clay minerals, biomass, modified carbon materials, and metal oxide materials. Although these materials have good adsorption effects, they also have certain problems, such as low selection of adsorption performance, high doping cost of metal materials, easy to cause secondary pollution of water bodies, and difficult recycling of adsorbent materials. Therefore, it is necessary to find a low-cost, pollution-free and easy-to-recycle modified composite adsorbent.
[0004] Porous geopolymers (PGs) are a new type of inorganic non-metallic material, which is a sustainable, safe and cost-effective green alkali-bonded porous concrete. It has excellent mechanical properties, high thermal stability, and the abundant global construction resources used in its production, low processing cost and simple synthesis procedures of these inorganic polymers, which can be used as a new type of environmentally friendly adsorbent. Many construction and industrial residual raw materials, such as fly ash, waste glass, red mud, coal ultrafine fly ash, and blast furnace slag are raw materials for the preparation of geopolymers, which not only reduces production costs but also increases the added value of waste utilization. So far, porous geopolymers have potential in water treatment and purification. Shell materials are rich in calcium and can be used as an ideal calcium source for modification. Eggshells and oyster shells are produced in large quantities in my country every year, but they are usually treated as kitchen waste, so there is great potential for cost reduction. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an adsorbent using industrial solid waste and kitchen waste as raw materials, which is used to deal with the phosphorus crisis and solve the problem of eutrophication of water bodies, so as to solve the problems raised in the above background technology.
[0006] The invention uses industrial solid waste fly ash and slag as raw materials, utilizes kitchen waste egg shells and oyster shells as pore-forming agents and adsorption sites, and adopts mechanical slow stirring combined with suspension polymerization to prepare geopolymer microspheres, thereby realizing the recovery of phosphate in water.
[0007] To achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing a geopolymer microsphere adsorbent. Based on the polymerization process of fly ash and slag under alkaline conditions and the strong adsorption capacity of egg shells and oyster shells after high-temperature calcination for phosphorus, the present invention adopts a mechanical slow stirring assisted high-temperature suspension polymerization method to prepare geopolymer microspheres, which are convenient for recycling and reuse for the adsorption of phosphate in water bodies. The appropriate mechanical stirring speed during the suspension polymerization process can control the residence time of the slurry in dimethyl silicone oil, while avoiding the separation of substances in the slurry. Since egg shells and oyster shells decompose after high-temperature calcination, they can replace the pore-forming agent in the geopolymer process, and the calcined calcium oxide provides abundant adsorption sites for the adsorption of phosphate.
[0008] The preparation method of the geopolymer microsphere adsorbent specifically comprises the following preparation steps: (1) Wash, dry, and crush the eggshell or oyster shell, and sieve through a 100-mesh sieve. Mix the fly ash and slag with the eggshell powder or oyster shell powder, and then add it to a certain concentration of alkaline activator aqueous solution to obtain a mixture slurry;
[0009] (2) Stirring the mixture slurry obtained above at a certain speed for 5-15 minutes to ensure that the eggshell powder / oyster powder is evenly distributed in the fly ash-slag slurry, setting a suitable stirring paddle speed and height in the dimethyl silicone oil to avoid separation of the mixture in the slurry during the polymerization process, opening the beaker valve while stirring, and adding the mixture slurry dropwise into the dimethyl silicone oil at 60-150° C., and obtaining polymer microspheres by mechanical slow stirring-suspension polymerization method; and curing at 40-100° C. for three days to obtain cured geopolymer microspheres;
[0010] (3) The solidified geopolymer microspheres are calcined in a tubular furnace at a certain temperature for 2 hours under a nitrogen atmosphere to obtain a geopolymer microsphere adsorbent.
[0011] Furthermore, in step (1), the aqueous solution of the alkaline activator is a 0.5 mol / L sodium hydroxide solution.
[0012] Furthermore, in step (1), the mass ratio of the total mass of the fly ash and slag to the eggshell powder / oyster shell powder is 10:1-10:5 (g:g).
[0013] Preferably, in step (1), the mass ratio of the total mass of the fly ash and slag to the eggshell powder / oyster shell powder is 10:3 (g:g).
[0014] Furthermore, in step (1), the mass ratio of the mixture slurry obtained in step (1) to the aqueous solution of the alkaline activator is 10:4-15:4.
[0015] Furthermore, in step (2), the speed of mechanically stirring the dimethyl silicone oil is controlled at 100-500 rpm.
[0016] Preferably, the speed of mechanically stirring the dimethyl silicone oil in step (2) is controlled at 300 rpm.
[0017] Furthermore, in step (3), the calcination temperature in the tubular furnace is 600-800°C.
[0018] The present invention also provides application of the geopolymer microsphere adsorbent prepared by the preparation method in adsorbing phosphate materials.
[0019] The invention is based on the fact that the main component of eggshell or oyster shell is calcium carbonate, which has been proved to have strong adsorption capacity for phosphate after high-temperature calcination, and calcium carbonate is also a pore-forming agent in the synthesis process of geopolymer. The invention uses suspension polymerization to synthesize geopolymer microspheres, wherein the eggshell or oyster shell is both an adsorption site for phosphorus and a pore-forming agent in the material synthesis process, thereby reducing the synthesis cost, creating a porous structure for the polymer microspheres, and enhancing the adsorption effect.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts kitchen waste egg shells and oyster shells as pore-forming agents and adsorption sites in the adsorption process, and adopts a mechanical slow stirring assisted high-temperature polymerization ball forming method in the ball forming process to ensure the dispersion of egg shell or oyster shell powder on microspheres during the polymer ball forming process, thereby improving the final adsorption performance.
[0021] The invention has low preparation cost and little environmental pollution, and the required raw materials are industrial solid waste and kitchen waste, thus turning waste into treasure.
[0022] The microsphere adsorbent prepared by the present invention is easy to recycle, which solves the disadvantage that powdered adsorbent materials are difficult to recycle. It can also be used as a column filling material in water treatment process, which has more practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a physical picture of the geopolymer microspheres prepared in Example 3 of the present invention; Figure 2 The effect of the amount of egg shell used in the synthesis process on the adsorption performance of the prepared microsphere adsorbent; Figure 3The effect of the stirring speed of the dimethyl silicone oil on the adsorption performance of the prepared microsphere adsorbent during suspension polymerization. Figure 4 To study the effect of the amount of oyster shell used in the synthesis process on the adsorption performance of the prepared microsphere adsorbent; Figure 5 The effect of the stirring speed of the dimethyl silicone oil on the adsorption performance of the prepared microsphere adsorbent during suspension polymerization. Figure 6 It is the technical roadmap of the present invention. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The preparation method of the geopolymer microsphere adsorbent of the present invention, the technical roadmap is as follows Figure 6 shown. Example 1
[0026] First, the eggshell was washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 1 g of eggshell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the eggshell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 300 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120 ° C to obtain polymer microspheres by suspension polymerization. And cured at 80 ° C for three days. The cured geopolymer microspheres were calcined at 800 ° C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70 ° C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 hours to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtering with a 0.45 μm microporous membrane. Example 2
[0027] First, the eggshells were washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 2 g of eggshell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the eggshell powder was evenly distributed in the slag slurry. After 15 minutes, the appropriate stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 300 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120°C to obtain polymer microspheres by suspension polymerization. And cured at 80°C for three days. The cured geopolymer microspheres were calcined at 800°C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70°C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtering with a 0.45 μm microporous membrane. Example 3
[0028] First, the eggshell was washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 3 g of eggshell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the eggshell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 300 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120°C to obtain polymer microspheres by suspension polymerization. And cured at 80°C for three days. The cured geopolymer microspheres were calcined at 800°C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70°C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane.
[0029] The actual picture of the geopolymer microspheres prepared in this example is as follows Figure 1 As shown, the geopolymer microspheres prepared by the present invention have good sphericity, are relatively uniform in size, and have a relatively rough surface, indicating that after high-temperature calcination, the eggshells and oyster shells are fully decomposed to produce a porous structure. Example 4
[0030] First, the eggshells were washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 4 g of eggshell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the eggshell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 300 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120°C to obtain polymer microspheres by suspension polymerization. And cured at 80°C for three days. The cured geopolymer microspheres were calcined at 800°C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70°C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane. Example 5
[0031] First, the eggshells were washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 5 g of eggshell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the eggshell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 300 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120°C to obtain polymer microspheres by suspension polymerization. And cured at 80°C for three days. The cured geopolymer microspheres were calcined at 800°C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70°C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane. Example 6
[0032] First, the eggshell was washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 3 g of eggshell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the eggshell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 100 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120°C to obtain polymer microspheres by suspension polymerization. And cured at 80°C for three days. The cured geopolymer microspheres were calcined at 800°C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70°C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane. Example 7
[0033] First, the eggshell was washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 3 g of eggshell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the eggshell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 300 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120°C to obtain polymer microspheres by suspension polymerization. And cured at 80°C for three days. The cured geopolymer microspheres were calcined at 800°C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70°C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane. Example 8
[0034] First, the eggshells were washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 3 g of eggshell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the eggshell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 500 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120°C to obtain polymer microspheres by suspension polymerization. And cured at 80°C for three days. The cured geopolymer microspheres were calcined at 800°C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70°C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane. Example 9
[0035] First, the oyster shells were washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 1 g of oyster shell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the oyster shell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 300 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120 ° C to obtain polymer microspheres by suspension polymerization. And cured at 80 ° C for three days. The cured geopolymer microspheres were calcined at 800 ° C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70 ° C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane. Example 10
[0036] First, the oyster shells were washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 2 g of oyster shell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the oyster shell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 300 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120°C to obtain polymer microspheres by suspension polymerization. And cured at 80°C for three days. The cured geopolymer microspheres were calcined at 800°C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70°C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane. Embodiment 11
[0037] First, the oyster shells were washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 3 g of oyster shell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the oyster shell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 300 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120 ° C to obtain polymer microspheres by suspension polymerization. And cured at 80 ° C for three days. The cured geopolymer microspheres were calcined at 800 ° C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70 ° C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane. Example 12
[0038] First, the oyster shells were washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 4 g of oyster shell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the oyster shell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 300 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120 ° C to obtain polymer microspheres by suspension polymerization. And cured at 80 ° C for three days. The cured geopolymer microspheres were calcined at 800 ° C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70 ° C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane. Example 13
[0039] First, the oyster shells were washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 5 g of oyster shell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the oyster shell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 300 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120 ° C to obtain polymer microspheres by suspension polymerization. And cured at 80 ° C for three days. The cured geopolymer microspheres were calcined at 800 ° C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70 ° C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane. Embodiment 14
[0040] First, the oyster shells were washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 3 g of oyster shell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the oyster shell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 100 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120°C to obtain polymer microspheres by suspension polymerization. And cured at 80°C for three days. The cured geopolymer microspheres were calcined at 800°C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70°C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane. Embodiment 15
[0041] First, the oyster shells were washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 3 g of oyster shell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the oyster shell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 300 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120 ° C to obtain polymer microspheres by suspension polymerization. And cured at 80 ° C for three days. The cured geopolymer microspheres were calcined at 800 ° C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70 ° C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane. Example 16
[0042] First, the oyster shells were washed with deionized water, then dried and crushed into powder and sieved with a 100-mesh screen. 8 g of fly ash, 2 g of slag mixture and 3 g of oyster shell powder were mixed at room temperature, and 4 mL of 0.5 mol / L sodium hydroxide aqueous solution was added. The mixture was stirred at 800-1200 rpm to ensure that the oyster shell powder was evenly distributed in the slag slurry. After 15 minutes, the stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 500 rpm to avoid separation of the mixture in the slurry during the polymerization process. The beaker valve was opened while stirring, and the slurry was added dropwise to the dimethyl silicone oil at 120°C to obtain polymer microspheres by suspension polymerization. And cured at 80°C for three days. The cured geopolymer microspheres were calcined at 800°C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70°C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 h to reach adsorption equilibrium. The remaining phosphate concentration was detected after filtration with a 0.45 μm microporous membrane. Comparative Example
[0043] At room temperature, 8 g of fly ash and 2 g of slag mixture were added with 4 mL of 0.5 mol / L sodium hydroxide aqueous solution. The stirring paddle speed in the dimethyl silicone oil during the suspension polymerization process was set to 300 rpm. The beaker valve was opened while stirring, and the mixture was added dropwise into the dimethyl silicone oil at 120°C to obtain polymer microspheres by suspension polymerization. The microspheres were cured at 80°C for three days. The cured geopolymer microspheres were calcined at 800°C for 2 hours in a tubular furnace under a nitrogen atmosphere. The product was washed with deionized water and dried at 70°C. 0.2 g of adsorbent was added to 100 mL of phosphate solution (50 mg P / L), and the mixture was shaken at 200 rpm for 12 hours to reach adsorption equilibrium. The residual phosphate concentration was detected after filtration with a 0.45 μm microporous membrane.
[0044] The phosphorus adsorption amounts of Examples 1 to 5 are as follows: Figure 2 As shown in FIG. 1 , when the mass ratio of the fly ash-slag mixture to the egg shell powder is 10:3, the prepared polymer microspheres have the highest phosphorus adsorption capacity; the phosphorus adsorption capacity of Examples 6-8 is as follows Figure 3 As shown in FIG. 1 , when the stirring blade speed in the dimethyl silicone oil is set to 300 rpm, the prepared polymer microspheres have the highest phosphorus adsorption amount. Figure 4 As shown in Figure 1, when the mass ratio of the fly ash-slag mixture to the oyster shell powder is 10:3, the prepared polymer microspheres have the highest phosphorus adsorption capacity. Figure 5As shown, when the stirring paddle speed in dimethyl silicone oil is set to 300 rpm, the prepared polymer microspheres have the highest phosphorus adsorption amount.
[0045] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0046] It should be noted that the above content only illustrates the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a geopolymer microsphere adsorbent, characterized in that: The following steps are involved: (1) washing, drying, crushing and passing eggshells or oyster shells through a 100-mesh sieve to obtain eggshell powder or oyster shell powder; mixing fly ash and slag with the eggshell powder or oyster shell powder, and then adding the mixture to an aqueous solution of an alkali activator to obtain a mixture slurry; (2) After stirring the mixture slurry for 5-15 minutes, the valve is opened while stirring to add the mixture slurry dropwise into the stirred dimethyl silicone oil at 60-150°C, and then solidify it at 40-100°C for three days to obtain solidified geopolymer microspheres; (3) The solidified geopolymer microspheres were calcined in a tubular furnace under a nitrogen atmosphere for 2 hours to obtain a geopolymer microsphere adsorbent.
2. The method for preparing a geopolymer microsphere adsorbent according to claim 1, characterized in that: In step (1), the mass ratio of the total mass of fly ash and slag to the mass ratio of eggshell powder or oyster shell powder is 10:1-10:
5.
3. The method for preparing a geopolymer microsphere adsorbent according to claim 1, characterized in that: In step (1), the aqueous solution of the alkaline activator is a 0.5 mol / L sodium hydroxide solution.
4. The method for preparing a geopolymer microsphere adsorbent according to claim 1, characterized in that: In step (1), the mass ratio of the mixture slurry obtained in step (1) to the aqueous solution of the alkaline activator is 10-15:
4.
5. The method for preparing a geopolymer microsphere adsorbent according to claim 1, characterized in that: In step (2), when the mixture slurry is added dropwise into the dimethyl silicone oil, the stirring speed of the dimethyl silicone oil is controlled at 100-500 rpm.
6. The method for preparing a geopolymer microsphere adsorbent according to claim 1, characterized in that: In step (3), the calcination temperature is 600-800°C.
7. Use of the geopolymer microsphere adsorbent prepared by the preparation method according to any one of claims 1 to 6 in materials for adsorbing phosphate.
Citation Information
Patent Citations
Preparation method and application of porous geological polymer microspheres
CN107973559A
Modified geopolymer-zeolite with nitrogen and phosphorus removal function as well as preparation method and application of modified geopolymer-zeolite
CN115350692A
Geopolymer adsorbent with hierarchical porous structure as well as preparation method and application of geopolymer adsorbent
CN117582959A